'Only connect': reflections on technology and transference. Issue 3 (1st September 2020) - Zuppardi, Sam
ABSTRACT: This paper reflects on some of the author's experiences conducting psychoanalytic psychotherapy remotely during the coronavirus pandemic. The author takes E M. Forster's famous epigraph 'Only connect' as a starting point for reflecting on the nature of connecting in therapy when that work is mediated by technology. In particular, the author discusses his uncertainty about the impact of a digital format on the transference relationship. Three vignettes from the author's clinical work with adolescents are presented to expand upon this theme, before the author concludes that a transference relationship can survive, and sometimes thrive, across a digital distance.